The Folk Superiority in the Humour of the Original and Sabah Version of Abu Nawas Tales: (Superioriti Rakyat dalam Lelucon Cerita Abu Nawas Asal dan Cerita Abu Nawas Versi Sabah) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2014)
The focus of this paper is to analyse the elements of folk superiority in both versions of Abu Nawas tales based on the Theory of Superiority. This study also attempts to track the spreads of Abu Nawas tales to Sabah. The tales of Abu Nawas are categorised as humorous tales from Arab and Persia amongst the folk-literature scholars of Malaysia. The spreads of Abu Nawas tales from Arab, Persia or India to the Malay Archipelago are closely linked to the spreads of Islam to this region in the 15thcentury. Drawing from field trips to collect folk tales in various districts of Sabah, it was noted that Abu Nawas tales are not only popular among the Muslim natives of Sabah like the Bruneian, Bajau and Suluk but also among the non Muslim natives of Sabah, like the Kimaragang, Rungus and Murut ethnic groups. However, In doing so, the feeling of folk superiority that was hidden in the humour of Abu Nawas tales will be revealed to the readers.Keywords: Abu Nawas, humorous tales, Theory of Superiority, folk superiority